Response mechanism of growth and gypenosides content for Gynostemma longipes cultivated at two altitude habitats to fine root morphological characteristics - Li, Doudou; Li, Gang; Xi, Benye; Gan, Jiaxia; Wen, Dingmei; Cao, Feng; Suo, Fengmei; Li, Jincan; Ma, Baiping; Guo, Baolin (Frontiers in Plant Science, 2023)
Fine roots are the critical functional organs of plants to absorb water and nutrients from the soil environment, while the relation between fine root morphological characteristics and yield & quality has received less attention for medicinal plants. Therefore, we investigated the relationship between fine root morphological characteristics and biomass & gypenosides content. We explored the primary environmental drivers of fine root indicators for Gynostemma longipes from three provenances cultivated at two altitude habitats. At the end of the growing season, compared with the low-altitude habitat, the underground biomass of G. longipes in the high-altitude habitat increased significantly by 200%~290% for all three provenances. The response of gypenosides content to different altitude habitats varied with provenance and plant organs. The biomass of G. longipes strongly depended on the fine root characteristic indicators (P < 0.001), fine root length density, and fine root surface area. Our results also showed that the harvest yield of G. longipes could be effectively increased by promoting the growth of fine roots per unit leaf weight (P < 0.001, R2 = 0.63). Both fine root length density and fine root surface area had strong positive correlations with soil nutrient factors (R2 > 0.55) and a strong negative correlation with soil pH (R2 > 0.48). In a word, the growth of G. longipes is strongly controlled by the fine root morphological characteristics through the response of fine roots to soil nutrient factors and pH. Our findings will help to deepen the understanding of the root ecophysiological basis driven by soil factors for the growth and secondary metabolites formation of G. longipes and other medicinal plants under changing habitat conditions. In future research, we should investigate how environmental factors drive plant morphological characteristics (e.g., fine roots) to affect the growth & quality of medicinal plants over a longer time scale.